(untitled) (Studia Prawnicze / The Legal Studies, 1985)
The aim of the work is to reveal and typologically arrange basic meanings of legal terms denoting or expressing somebody’s right. Legal provisions and opinions formulated in the doctrine constitute the research material. The author assumes that provisions comprised in legal texts perform an expressive function stimulating human behaviour and informative function. While discussing the sense of the term “right” and related terms the author uses a notion of a norm of procedure in a wide sense of it as a notion equal to a rule of procedure. The discussion is carried out at the level of legal and juridical language and not at the level of logical analysis of those languages. Thus, the definition of the meaning of permission and indifference formulated in deontic logic is not treated as starting point, although the aim of the work is, among others, to verify methodological assumptions of logic in the light of a descriptive and pragmatic analysis of legal and juridical language. The main part of the work is a catalogue of basic meanings attached to the term “right” in a legal discourse and the typology of rights. In the final part of the work the author presents three basic concepts of relations between rights and obligations: concept of correlation, concept of conjunction of rights and obligations, concept reducing the notion of obligation to negation of right or certain consequences of obligation.